Achromatic beam deflector with electrodynamic phased arrays - Jungkwuen An; Young Kim; Yunhee Kim; Hoon Song; Chunghwan Jung; Kanghee Won; Junsuk Rho; Hong-Seok Lee (Light: Science & Applications)
Abstract Since flat optics has the feature to implement a compact system, they are widely used in various applications to replace bulky refractive optics. However, they suffer from chromatic aberrations due to dispersion, limiting their effectiveness to a narrow wavelength range. Consequently, diffractive optics has been applied for dynamic beam steering within a specific wavelength region or for static steering across multiple wavelengths. This limitation has made it challenging to implement dynamic beam steering in full-color display applications. To address this issue, we developed a multi-wavelength-based optical architecture that mitigates chromatic aberrations. This system incorporates color-selective retarders, half-wave plates, polarization plates, and beam deflectors. We experimentally demonstrated an achromatic beam deflector using a dynamic phase array in transmission mode, achieving continuous tunable beam steering over multiple wavelengths at 460, 520, and 638 nm.